1999
DOI: 10.21273/jashs.124.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Potato PVYo Coat Protein and cryV-Bt Genes in Potato

Abstract: The codon-modified cryV-Bt gene (cryV-Bt) from Bacillus thuringiensis subsp. kurstaki Berliner, which is specifically toxic to Lepidoptera and Coleoptera insects, and a potato virus Yo coat protein gene (PVYocp), in which the aphid transmission site was inactivated, were cotransformed into potato (Solanum tuberosum<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The bioassay method used was based on the assumption that the level of Cry protein in excised leaves was similar to that in the foliage of intact plants. The same assumption has been made in similar studies involving PTM bioassays (Ebora et al, 1994;Jansens et al, 1995;Westedt et al, 1998;Beuning et al, 2001;Douches et al, 1998Douches et al, , 2002Li et al, 1999;Davidson et al, 2002Davidson et al, , 2004, and has been validated by the observed high correlation between excised leaves and intact plants for growth of PTM larvae in response to cry gene expression (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…In potato, it is often desirable to couple high-level expression of the transgene in foliage with no expression in tubers. Constitutive promoters have been used to drive cry gene expression in all previous studies targeting PTM resistance in transgenic potatoes (Douches et al, , 2002Jansens et al, 1995;Cañedo et al, 1999;Li et al, 1999;Chakrabarti et al, 2000;Mohammed et al, 2000;Davidson et al, 2002Davidson et al, , 2004. Since PTM generally infests foliage of potato crops prior to the tubers (Foot, 1979), preventing foliar infestation may be sufficient to avoid tuber infestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To contribute an additional component to integrated pest management, the development of transgenic potatoes that express genes encoding insecticidal compounds has been investigated (Meiyalaghan et al 2005). The use of cry genes from the soil bacterium, Bacillus thuringiensis, has been especially successful (e.g., Jansens et al 1995;Douches et al 1998;Li et al 1999;Davidson et al 2002Davidson et al , 2004Meiyalaghan et al 2006). However, the transfer of native cry genes to plants has often resulted in inadequate gene expression.…”
Section: Introductionmentioning
confidence: 99%